Financial development and economic performance: Malaysian experience / Latifah Abdullah - Abdullah, Latifah (2006)
The purpose of this study is to examine the correlation between financial development and economic performance based on Malaysian experience during year 1971 to 2000. It will highlight about financial development as well as about financial development features then will cover about economic performance in this nation. By do some analyzing on the factors that contributes towards this matter, an assumption can be conclude in the end. Financial development generally leads to economic growth which suggests that financial deepening has yielded a more prosperous economy. This shows that financial development stimulates economic growth and, simultaneously, economic growth propels financial development. Financial deepening contributes more to the causal relationships in the developing countries which implies that the developing countries have more room for financial and economic improvement. Here also find that financial development enhances growth through a more rapid capital accumulation and technological change.